Blockchain technology in international business: changing the agenda for global governance - Hooper, Amanda; Holtbrügge, Dirk (Review of International Business and Strategy, 2020)
Purpose: Blockchain technology has extended beyond the border of cryptocurrency and taken hold in various areas of international business. This study aims to analyze the impacts of blockchain on international business and the resulting challenges and implications for global governance. Design/methodology/approach: The analysis of multiple blockchain applications in international finance, banking and insurance, supply chain management and logistics and marketing and advertising shows that the use of blockchain in international business has different impacts on global governance. Findings: Although the protection of property rights can be improved and transaction costs can be reduced, the effects on other functions of global governance are more ambivalent. Research limitations/implications: As a recommendation for future studies, the need for more multidisciplinary and empirical research is proposed. Practical implications: As the technology disrupts business activities, it also affects the governance of these activities on a global scale. Suggestions for the future regulation of blockchain applications in international business are developed. Originality/value: Blockchain technology has extended beyond the border of cryptocurrency and taken hold in various areas of international business. This study aims to analyze the impacts of blockchain on international business and the resulting challenges and implications for global governance. The application of blockchain technology in international business across multiple industries is explored in order to draw conclusions about its impacts on global governance. It is determined that blockchain brings about both challenges and benefits for global governance.
CRIS-Team Scopus Importer:2020-04-21
Keywords: Bitcoin; Blockchain; Distributed-ledger technology; Global governance; International business; Smart contracts